The Impact of Accounting Fundamentals and Macroeconomic Indicators on Manufacturing Companies' Stock Prices - Van hyung Shih; Chien Hoang (Journal La Bisecoman, 2021)
The aim of this research is to ascertain if accounting fundamentals and macroeconomic indicators have an effect on stock prices. In this research, a quantitative method was used. The population of this research includes manufacturing firms listed on the Stock Exchange, with a sample size of ten companies collected through secondary data during the 2019-2020 quarter. Scale of data measurement using a ratio scale. The findings indicated that inflation and interest rate macroeconomic variables had little impact on stock values. Fundamentals of Accounting The return on equity and the price-earnings ratio both have a substantial beneficial impact on company prices